2016
DOI: 10.1074/jbc.m116.717884
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into the Catalytic Mechanism of Bacterial MraY from Enzyme Kinetics and Docking Studies

Abstract: Phospho-MurNAc-pentapeptide translocase (MraY) catalyzes the synthesis of Lipid I, a bacterial peptidoglycan precursor. As such, MraY is essential for bacterial survival and therefore is an ideal target for developing novel antibiotics. However, the understanding of its catalytic mechanism, despite the recently determined crystal structure, remains limited. In the present study, the kinetic properties of Bacillus subtilis MraY (BsMraY) were investigated by fluorescence enhancement using dansylated UDP-MurNAc-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 44 publications
(51 reference statements)
3
21
1
Order By: Relevance
“…It was found that increase of C55-P concentration increased the sensitivity of the assay to inhibition by tunicamycin. This finding corresponds to the Km discrepancies of MraY between different studies when different C55-P concentrations were used, which is addressed as the major message in our own study [ 34 ]. This FRET assay allowed the measurement of the fluorescence intensity ratio of the donor and acceptor, hence fluctuations in measurements that influence both the donor and acceptor fluorescence could be ruled out.…”
Section: Mraysupporting
confidence: 66%
See 4 more Smart Citations
“…It was found that increase of C55-P concentration increased the sensitivity of the assay to inhibition by tunicamycin. This finding corresponds to the Km discrepancies of MraY between different studies when different C55-P concentrations were used, which is addressed as the major message in our own study [ 34 ]. This FRET assay allowed the measurement of the fluorescence intensity ratio of the donor and acceptor, hence fluctuations in measurements that influence both the donor and acceptor fluorescence could be ruled out.…”
Section: Mraysupporting
confidence: 66%
“…It is worth noting that in this study, the kinetic values of BsMraY and its mutants were obtained by varying UDP-Mpp concentration between 3 and 6 mM while keeping C55-P at 1.1 mM. These concentrations are very high, and the K M values obtained were much higher than those of our own kinetic study [ 34 ]. The K cat value of the H289R mutant reported in this study decreased by three orders of magnitude.…”
Section: Mraymentioning
confidence: 68%
See 3 more Smart Citations